Oxidative Stress and Neuroinflammation as a Pivot in Drug Abuse. A Focus on the Therapeutic Potential of Antioxidant and Anti-Inflammatory Agents and Biomolecules - Pablo Berríos-Cárcamo; Mauricio Quezada; María Elena Quintanilla; Paola Morales; Marcelo Ezquer; Mario Herrera-Marschitz; Yedy Israel; Fernando Ezquer (MDPI AG, 2020)
Drug abuse is a major global health and economic problem. However, there are no pharmacological treatments to effectively reduce the compulsive use of most drugs of abuse. Despite exerting different mechanisms of action, all drugs of abuse promote the activation of the brain reward system, with lasting neurobiological consequences that potentiate subsequent consumption. Recent evidence shows that the brain displays marked oxidative stress and neuroinflammation following chronic drug consumption. Brain oxidative stress and neuroinflammation disrupt glutamate homeostasis by impairing synaptic and extra-synaptic glutamate transport, reducing GLT-1, and system Xc− activities respectively, which increases glutamatergic neurotransmission. This effect consolidates the relapse-promoting effect of drug-related cues, thus sustaining drug craving and subsequent drug consumption. Recently, promising results as experimental treatments to reduce drug consumption and relapse have been shown by (i) antioxidant and anti-inflammatory synthetic molecules whose effects reach the brain; (ii) natural biomolecules secreted by mesenchymal stem cells that excel in antioxidant and anti-inflammatory properties, delivered via non-invasive intranasal administration to animal models of drug abuse and (iii) potent anti-inflammatory microRNAs and anti-miRNAs which target the microglia and reduce neuroinflammation and drug craving. In this review, we address the neurobiological consequences of brain oxidative stress and neuroinflammation that follow the chronic consumption of most drugs of abuse, and the current and potential therapeutic effects of antioxidants and anti-inflammatory agents and biomolecules to reduce these drug-induced alterations and to prevent relapse.